Insightful view on the active sites of Ni/NixP for hydrogen evolution reaction. (March 2022) - Chen, Mingpeng; Liu, Di; Chen, Yuyun; Liu, Dong; Du, Xinyu; Feng, Jinxian; Zhou, Pengfei; Zi, Baoye; Liu, Qingju; Lo, Kin Ho; Chen, Shi; Wang, Shuangpeng; et al.
Highlights: The catalytic performance of Ni/Nix P-60/CC gradually improves in acid, but slightly reduces in alkali during the HER process. In-situ Raman spectroscopy verifies that the surface reconstruction doesn't happen during the HER process. In-situ Raman spectroscopy further reveals that the negatively charged P ions act as effective sites that trap the positively charged protons effectively. An authentic structure−activity relationship can be achieved by combined ex-situ and in-situ studies to figure out the actual origin for the HER process. Abstract: Low-cost and efficient electrocatalysts have been extensively studied for hydrogen evolution reaction (HER) in large-scale hydrogen production. However, the actual active sites on their surfaces in working condition have not been understood clearly. Herein, we carry out a systematic study to figure out the active sites on the Ni/Nix P hybrids grown on carbon cloth (Ni/Nix P/CC) for HER in both acidic and alkaline conditions, by a series of combined in-situ and ex-situ characterizations. Interestingly, we find that their current densities gradually increase (maximum: 106.1%) at a voltage of −0.16 V (vs. RHE) in acid, but show slight reduction in alkali at a voltage of −0.2 V (vs. RHE). Ex-situ studies show that Ni/Nix P/CC electrodes undergo significant morphology remodeling and surface reconstruction after working in both acid and alkali. However, in-situ Raman spectroscopy shows that the surface reconstruction does not happen during the HER process. Most importantly, in-situ Raman spectroscopy reveals that the negatively charged P ions act as active sites that attract the positively charged protons for HER. Our findings demonstrate that tracking the dynamic structure evolution may be significant to gain insightful understanding on the reaction mechanism, which shall provide meaningful guidance to the design of catalysts for practical applications. Graphical abstract: Image, graphical abstract